Ivory Arthroplasty for Trapeziometacarpal Joint Arthritis in Men: Analysis of Clinical Outcome and Implant Survival. (May 2022) - Vanmierlo, Bert; Buitenweg, John; Vanmierlo, Tim; Van Royen, Kjell; Bonte, Francis; Goubau, Jean
Background: Trapeziometacarpal arthroplasties are designed to restore an adequate level of mobility, stability, and grip strength. In this article, pain and functional and radiographic outcome of Ivory arthroplasty in male patients are investigated.Methods: Between 2005 and 2012, the Ivory arthroplasty was inserted in 21 male patients with degenerative trapeziometacarpal osteoarthritis, of which 14 patients were found eligible for inclusion. Mobility, grip strength, patient self-assessment (pain; Quick Disabilities of the Arm, Shoulder, and Hand [QuickDASH]), and radiographic outcome were measured. Twenty-two female patients who received an Ivory arthroplasty between 2005 and 2007 were included and underwent the same evaluation. Age at primary surgery, survival rate of the implant, and clinical outcome were compared between the 2 groups.Results : In both groups, QuickDASH score and mean pain sensation improved significantly. The improvement in mobility obtained significance in the female group. In the male group, 7 arthroplasties failed (mean follow-up of 65 months). In the female group, 3 of the 24 arthroplasties failed (mean follow-up of 123 months). Kaplan-Meier survival analysis demonstrated a significant lower implant survival in the male group.Conclusions: Decrease in muscle mass and decline in grip strength that postmenopausal women tend to experience might explain the significant difference in implant survival between sexes. In 4 of the 7 failed arthroplasties in the male group, no surgical revision was required. Trapeziometacarpal arthroplasty, even after radiographic failure, still served as a spacer, avoiding collapse of the thumb base. Nevertheless, the failure rate of the Ivory arthroplasty in male patients is high, and an alternative treatment should be considered.